2019
DOI: 10.2174/2213346106666191019144116
|View full text |Cite
|
Sign up to set email alerts
|

Green Protocols for the Synthesis of 3,3’-spirooxindoles – 2016- mid 2019

Abstract: Spirooxindoles, particularly 3,3’-spirooxindoles constitute a privileged structural scaffold owing to the intensive biological activities which they possess. Because of this over the last twenty years, a large number of methods were devised for their synthesis and some of these molecules have entered pre-clinical trials. Of late, methods for spirooxindole synthesis using green protocols have developed rapidly. Reactions based on multicomponent strategies using non-catalytic / biocatalytic pathways and those do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…[74][75][76] These ring systems have been used regularly as a scaffold in medicinal and agricultural chemistry. [77][78][79][80] Synthesis of spirooxindoles is an interesting subject in synthetic chemistry due to their pharmacological activities such as anticancer, anti-HIV, anti-tuberculosis, antifungal, antibacterial and anti-malarial properties.…”
Section: Introductionmentioning
confidence: 99%
“…[74][75][76] These ring systems have been used regularly as a scaffold in medicinal and agricultural chemistry. [77][78][79][80] Synthesis of spirooxindoles is an interesting subject in synthetic chemistry due to their pharmacological activities such as anticancer, anti-HIV, anti-tuberculosis, antifungal, antibacterial and anti-malarial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, reviews were reported on the synthesis of spirooxindole via green protocols. 28 In addition, several other reviews are available on the catalytic asymmetric synthesis of spirooxindole. [29][30][31] In the present review, we highlight the transition metal-catalyzed synthesis of spirooxindoles up to 2020.…”
Section: Introductionmentioning
confidence: 99%